Solid Fuel Exposure and Chronic Obstructive Pulmonary Disease in Never-Smokers - Long, HuanYu; Xing, ZhenZhen; Chai, Di; Liu, WeiMing; Tong, YaQi; Wang, YuXia; Ma, YaLi; Pan, MingMing; Cui, Jia; Guo, YanFei (Frontiers in Medicine, 2021)
Background: Chronic obstructive pulmonary disease (COPD) is a public health challenge globally. The burden of COPD is high in never-smokers but little is known about its causes. We aimed to find the prevalence and correlates of COPD in never-smokers, with a special focus on solid fuel exposure. Methods: We conducted a cross-sectional study in Western China. COPD was defined by FEV1/FVC < lower limits of normal (LLN). Descriptive statistics and multivariable logistic regression were used for analyses. Results: Six thousand two hundred and seventy one patients were enrolled between June 2015 and August 2016. The prevalence of COPD in never-smokers was 15.0% (95% confidence interval 14.1–15.9). The common independent predictors of COPD in never-smokers included age ≥60 years, exposure to solid fuel, living in a rural area and a history of tuberculosis. Participants with solid fuel exposure were 69% more likely to have COPD (adjusted odds ratio 1.69, 95% CI 1.41–2.04) than those without such exposure. In addition, we found a positive association between small airway dysfunction and solid fuel exposure (OR 1.35, 95% CI 1.18–1.53). Conclusions: This study confirmed the substantial burden of COPD among never-smokers and also defined the risk factors for COPD in never-smokers. Furthermore, we found a positive association between solid fuel exposure and COPD or small airway dysfunction.